2020
DOI: 10.1007/s43032-020-00237-z
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Reduces Embryonic Loss Rate and Ameliorates Trophoblast Apoptosis in Early Pregnancy of Mice with Polycystic Ovary Syndrome by Affecting the AMPK/PI3K/Akt/FoxO3a Signaling Pathway

Abstract: Reports in recent years have suggested that adiponectin (APN) improves insulin resistance and inhibits apoptosis by activating the AMP-activated protein kinase (AMPK) pathway and the PI3K/Akt signaling pathway after binding to its receptor. This study aims to explore the mechanism by which APN reduces embryo loss rate and trophoblast apoptosis in early pregnancy of mice with polycystic ovary syndrome (PCOS). PCOS mice were subcutaneously injected with APN (10 μg mg kg−1 day−1) on 11 consecutive days from the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The results of the present study demonstrated that FPR2 knockdown caused the phosphorylation of AKT and PI3K. AKT is the direct target protein of the PI3K signaling pathway and is associated with cell proliferation, differentiation, apoptosis and migration (44)(45)(46). Functional analyses in the present study revealed that FPR2 may be involved in the regulation of trophoblast function through the PI3K/AKT signaling pathway.…”
Section: Discussionsupporting
confidence: 53%
“…The results of the present study demonstrated that FPR2 knockdown caused the phosphorylation of AKT and PI3K. AKT is the direct target protein of the PI3K signaling pathway and is associated with cell proliferation, differentiation, apoptosis and migration (44)(45)(46). Functional analyses in the present study revealed that FPR2 may be involved in the regulation of trophoblast function through the PI3K/AKT signaling pathway.…”
Section: Discussionsupporting
confidence: 53%
“…In KGN human granulosa cells, AMPK signaling pathways is activated in response to berberine that is known to improve insulin sensitivity and ovulation function in PCOS patients (Li, et al 2020). Recently, Zhang et al showed that AMPK pathway is involved in the reduction of the embryo loss rate in response to adiponectin treatment in PCOS mice (Zhang, et al 2020). In the well-established DHEA-induced PCOS mouse model, expression of SIRT1 and activation of AMPK are largely enhanced in ovary suggesting that SIRT1 through AMPK activation could modulate autophagy in PCOS ovaries (Di Emidio, et al 2020).…”
Section: Pcosmentioning
confidence: 99%
“…The treatment of polyherbal syrup significantly improves the mRNA expression of AMPK and GLUT4 in the CHO cell line. The polyherbal syrup-activated AMPK expression in ovarian cells indicates that it can have the capacity to improve insulin resistance and regulate menstruation and promote ovulation by activating AMPK/PI3K/AKT/FoxO3 signaling pathway [ 51 , 52 ]. Also, the activation of AMPK down-regulates gluconeogenesis gene expression.…”
Section: Discussionmentioning
confidence: 99%